2020
DOI: 10.1021/acs.jpcb.0c01564
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Porous and Highly Crystallinity Vanadium Phosphorus Oxide Catalysts by Multifunctional Biomass-Based Deep Eutectic Solvents

Abstract: Deep eutectic solvents (DESs) as a novel class of ionic liquid analogues has been widely used in various fields. Herein, a multifunctional biomass-based DES composed of choline chloride (ChCl) and glucose (GLU) was synthesized and used for the modification of vanadium phosphorus oxide (VPO) catalyst, which is the sole catalyst for the selective oxidation of n-butane to maleic anhydride (MA) in industry. The DES is more green, cost-effective and efficient compared with traditional modifier (metal inorganics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…Herein, peaks were determined using Avantage software and the curve was fitted via Gaussian function. In literature exhibiting the binding energies associated with vanadium, characteristic peaks (V2p 3/2 ) are reported repeatedly (Figure 16a) [26,27]. The V2p 3/2 characteristic results obtained from the fitted curve correspond to the whole catalyst vanadium species V 5+ (VOPO 4 ) and V 4+ ((VO) 2 P 2 O 7 ).…”
Section: Characterization Of Precursors and Catalystsmentioning
confidence: 59%
See 2 more Smart Citations
“…Herein, peaks were determined using Avantage software and the curve was fitted via Gaussian function. In literature exhibiting the binding energies associated with vanadium, characteristic peaks (V2p 3/2 ) are reported repeatedly (Figure 16a) [26,27]. The V2p 3/2 characteristic results obtained from the fitted curve correspond to the whole catalyst vanadium species V 5+ (VOPO 4 ) and V 4+ ((VO) 2 P 2 O 7 ).…”
Section: Characterization Of Precursors and Catalystsmentioning
confidence: 59%
“…Additionally, these dopants have a bad effect on the environment. Therefore, we prepared a eutectic solvent from various metal dopants for a VPO catalyst [25][26][27]. The issues of poor crystallinity and limited active sites were solved by organic modifications and template strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies report results from theory (Hayyan, Tuinier) , as well as classical and ab initio molecular dynamics simulations (Atilhan, Aparicio, Kashyap, Hung, Chaumont, Banerjee, Pádua, Kirchner, Zahn, Paul, and Balasubramanian) to shed light on the structure, thermodynamics, and dynamics of DESs. X-ray and neutron scattering studies, sometimes in conjunction with molecular simulations, are reported to better understand DES structure (Triolo, Russina, Lewandowski, Brown, Atkin, Maginn, and Edler). Various spectroscopic techniques are used, sometimes in conjunction with simulations, to study solvation structure, dynamics, and diffusion (Mitra, Sen, Biswas, Pandey, Kuroda, Gurkan, and Baker). Other studies have focused on catalysis (Liu, Zhang), the effect of water on properties (Gutiérrez, Panzer), , electrodeposition (Magagnin), and fundamental thermodynamics and phase behavior (Coutinho, Marrucho). , …”
mentioning
confidence: 99%
“…26−30 Various spectroscopic techniques are used, sometimes in conjunction with simulations, to study solvation structure, dynamics, and diffusion (Mitra, Sen, Biswas, Pandey, Kuroda, Gurkan, and Baker). 31−37 Other studies have focused on catalysis (Liu, Zhang), 38 the effect of water on properties (Gutieŕrez, Panzer), 39,40 electrodeposition (Magagnin), 41 and fundamental thermodynamics and phase behavior (Coutinho, Marrucho). 42,43 The field of deep eutectic solvents is growing rapidly, and new DES compositions are being discovered along with the growth of a greater understanding of the physical chemistry of these fascinating fluids.…”
mentioning
confidence: 99%